Numerical investigation of 3D-printed metallic metamaterial for high energy absorption - Peng, Xiu (Nanyang Technological University, 2023)
The concept of 3D-printing from the additive manufacturing industry is a method of creating an architected 3-dimensional object layer-by-layer. The technology used was completely distinct from the conventional strategies, which was essential casting or machining. By arranging the structures and designing the unicell for each individual component, all driven and controlled by computer, the product of the printing will be very accurate. Architected metamaterials are materials with rationally designed structures that can achieve superior properties in terms of weight-to-strength ratio and material cost. By adjusting the parameter of the unicell accordingly, the physical properties of the printed structure will have various ways of presenting. And by using different ways of unicell assembly, the printed structure is identifying the key feature of mechanical metamaterials. 3D metamaterials were carried out with unreachable mechanical properties in natural materials, in the same manner with negative Poisson’s ratio, stiffness, and thermal expansion coefficient. The energy-absorbing metamaterials are effectively remaining lightweight, and able to load throughout the architecture. The newly developed unicell is not limited to pattern and adjusting single parameters. This kind of fabrication of the structure is concurrently making the metamaterials much lighter and with high energy absorption. The main purpose of this research is to design a high energy absorption structure by adjusting the parameters of the unicell. According to the metamaterial properties, their shape, geometry, size, orientation, and arrangements provide them with their special properties of energy absorption. Therefore, we will present an overview of the design of the unicell. We will build different structures with different parameters of the unicell, and we will compare the results of compression experiments in different directions, and with different parameters of the unicell.